Democracy and growth: An alternative empirical approach - Jian-Guang Shen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This paper proposes a "before-and-after" approach to empirical examination of the relationship between democracy and growth. Rather than the commonly used cross-country regression method, this paper compares the economic performances of forty countries before and after they became democracies or semi-democracies sometime within the last forty years.The empirical evidence indicates that an improvement in growth performance typically follows the transformation to democracy.Moreover, growth under democracy appears to be more stable than under authoritarian regimes. Interestingly, wealthy countries often experience declines in growth after a democratic transformation, while very poor nations typically experience accelerations in growth.Growth change appears to be negatively related to the initial savings ratio and positively related to the export ratio to GDP.Partial correlation between growth change and primary school or secondary school enrollments and the ratio of government expenditure to GDP is not identified.
URN:NBN:fi:bof-201408071966
Keywords: O40; O57; O40; O57; 330; Democracy; economic growth